PORTFOLIO ASSESSMENT BASED INSTRUCTION IN TEACHING WRITING FOR SENIOR SECONDARY SCHOOL IN MAKASSAR - Nopitasari, Dewi (International Journal of Research on English Teaching and Applied Linguistics, 2024)
The objectives of this research were to find out whether or not the use of portfolio assessment based instruction improves the students’ writing skill. This research employed Experimental Research design. The sample consisted of 36 students of grade X SMA Negeri 5 Makassar academic year of 2022/2023. The data were collected through the instruments: writing test for the students’ writing skill.  Data on the students’ writing skill were analyzed using descriptive and inferential statistics. The results of the research were: the use of portfolio assessment based instruction in teaching writing improved the students writing skill. The mean score of students in post-test (2.8) was higher  than pre-test (1.6) or increased 1.2 points. These conditions show that there was the improvement of students’ achievement in writing toward the application of portfolio assessment in ELT, particularly in the students’ writing class. It can be concluded that the use of portfolio assessment based is effective to be implemented in improving the students’ writing skills.